Molecular definition of the transplantation antigens. (1st May 2018) - Parham, Peter
Abstract : In the first half of the 20th century, the major histocompatibility complex (MHC) of the laboratory mouse, the H‐2 complex, was defined by a combination of serology and genetics. In the second half of the 20th century, its human counterpart, the human leukocyte antigen (HLA) complex was similarly defined and shown to mediate rejection of allogeneic kidney grafts. The clinical relevance of the transplantation antigens created the field of transplant immunology, which aimed to reduce graft rejection by HLA matching of transplant donors and recipients, and to use immunosuppressive drugs to prevent and treat rejection. Because tissue transplantation is not a natural phenomenon, the relevance of the MHC for immunology and immune defense against microbial pathogens was frequently questioned. In the 1970s, the general observation that cytotoxic T‐cell responses to viral infection required recognition of both a viral antigen and a transplantation antigen argued for the immunological importance of the MHC. Proving this point was not achieved until close to the end of the 20th century. This required detailed biochemical and structural analysis of the transplantation antigens, the viral antigens, and the T‐cell receptors that recognized them. This century of research culminated in 1996 with the three‐dimensional crystallographic structure of the complex of these three components. In this complex is MAC, the very first HLA antigen to be detected and now more formally known as HLA‐A*02:01. Abstract : Characterizing erythrocyte antigens facilitated blood transfusion and catalyzed exploration for antigens that could be matched to transplant other tissues. One genetic locus, human HLA/mouse H‐2, was found to cause graft rejection and to come in numerous forms. Determining the molecular basis of these antigens became a biochemists' grail. In unanticipated ways, their work shone a searchlight on fundamental workings of the immune system.